Interaction between the two cyclones of November 1977 over Indian seas - BALASUBRAMANIAM, V.; JAYANTHI, N. (MAUSAM, 1982)
The 81multaneous presence of two severe cyclonic storms one over Bay of Bengal and the other over Arabian Sea in November 1977 was a rare event. Their movement was contrary to the upper steering flow and the axis connecting their centres underwent a cyclonic rotation about a all in fixed point for three days till the Bay cyclone crossed coast. The ratio of the distances of their centre with to this point remained constant. The ratio of the angular rotation of this axis calculated by Brand's formula to the observed value was about 1.5 on all the 3 days.